Investigation on Machining of Holes and Channels on Borosilicate and Sodalime Glass Using μ-ECDM Setup. (2016) - Madhavi, J. Bindu; Hiremath, Somashekhar S.
Abstract: Electro Chemical Discharge Machining (ECDM) is a non-conventional machining process used to machine various conducting and non-conducting engineering materials. The non-conventional machining processes, uses some form of energy to machine materials. These some form of energies includes mechanical, thermal, chemical etc. Some of the mechanical machining processes are Water Jet Machining (WJM), Abrasive Jet Machining (AJM), Ultra Sound Machining (USM) etc., thermal machining processes are Electro Discharge Machining (EDM), Ion Beam Machining (IBM), Plasma Arc Machining (PAM), Laser Beam Machining (LBM) etc., and chemical machining processes are Electro Chemical Machining (ECM), Electro Chemical Grinding (ECG), etc. EDM and ECM machining processes are well developed and established commercially. Currently the main focus is on hybrid machining processes to utilize the advantages of one and overcome the disadvantages of others. ECDM is one such process which combines the features of EDM and ECM to machine non-conducting materials. ECDM process is mainly used for machining, scribing hard and brittle non-conducting materials like soda lime glass, borosilicate glass, PMMA material, silicon wafers etc. In the present work, experiments are conducted to machine holes and channels with a developed μ-ECDM setup. Design of Experiments (DOE) is used to plan and conduct the experiments. Optimized combinations of process parameters- voltage, duty factor and electrolyte concentration are obtained for responses- maximum Material Removal Rate (MRR), minimum Tool Wear Rate (TWR) and Radial Over Cut (ROC) are obtained using main effect plots. Repeatable holes and channels are machined using the obtained optimized parameter for maximum MRR. The response- diameter of micro holes of 0.92 mm, micro channels of length 14 mm, 0.34 mm and 0.63 mm width are obtained on borosilicate and sodalime glass with tool diameter 0.3 mm of tungsten carbide and tungsten copper alloy material.